2013
DOI: 10.1371/journal.pone.0074171
|View full text |Cite
|
Sign up to set email alerts
|

Cotrimoxazole Prophylaxis and Risk of Severe Anemia or Severe Neutropenia in HAART-Exposed, HIV-Uninfected Infants

Abstract: BackgroundProphylactic cotrimoxazole is recommended for infants born to HIV-infected mothers. However, cotrimoxazole may increase the risk of severe anemia or neutropenia.MethodsWe compared the proportion of HIV-exposed uninfected (HIV-EU) infants experiencing incident severe anemia (and separately, severe neutropenia) between a prospective cohort receiving prophylactic cotrimoxazole from 1 to 6 months vs. infants from two prior trials who did not receive cotrimoxazole. Infants were from rural and urban commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…9 However, a previous study comparing infants in the Mma Bana and MASHI studies who did not receive cotrimoxazole with a cohort that received both cotrimoxazole and ART showed no difference in the risk of severe neutropenia by cotrimoxazole exposure. 13 In our study, none of the cases of infant neutropenia were symptomatic, a finding consistent with other studies. 1,7 The clinical significance of neutropenia is still largely unknown, though a study among HIV-1-exposed European infants reported staphylococcal infections related to neutropenia.…”
Section: Discussionsupporting
confidence: 93%
“…9 However, a previous study comparing infants in the Mma Bana and MASHI studies who did not receive cotrimoxazole with a cohort that received both cotrimoxazole and ART showed no difference in the risk of severe neutropenia by cotrimoxazole exposure. 13 In our study, none of the cases of infant neutropenia were symptomatic, a finding consistent with other studies. 1,7 The clinical significance of neutropenia is still largely unknown, though a study among HIV-1-exposed European infants reported staphylococcal infections related to neutropenia.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study on the effects of CPT on hematologic outcomes in HEU infants in Botswana showed that severe anemia and neutropenia were rare among HEU infants and there was no association between CPT and either outcome [29]. Our research confirms the low frequency of severe neutropenia in HEU infants, while the difference in frequency of severe anemia may be attributable to the different population studied.…”
Section: Discussionsupporting
confidence: 73%
“…Cotrimoxazole may directly impact erythropoiesis, causing a reduction in red cell number, yet simultaneously lead to increased Hb levels because of its beneficial effects at reducing malaria and other infections. [29][30][31] Even still, our study results suggest a cause for concern, as HIV-associated anemia has also been shown to increase the risk of mortality. 13 Concern about the high prevalence of anemia in our cohort is heightened by the fact that many HIV-infected and HIVexposed uninfected children in Mozambique are at increased risk for other processes which affect the production of red blood cells, such as nutritional deficiencies from chronic malnutrition, chronic blood loss from helminth infections, and endemic infections such as malaria and TB.…”
Section: Discussionmentioning
confidence: 65%